ANALISIS PERBANDINGAN METODE FUZZY VIKOR DAN TOPSIS UNTUK APLIKASI SISTEM PENGAMBILAN KEPUTUSAN - Ezarfelix, Juandreas; Manik, Ngarap Im; Hasani, Muhammad Fikri (Journal of Information System, Applied, Management, Accounting and Research, 2024)
In today’s complex modern life, decision making plays a vital role. To assist in better decision making, a decision support system (DSS) application implementing Fuzzy VIKOR and Fuzzy TOPSIS methods has been developed. The application allows users to input evaluation criteria and alternatives, generating reliable and consistent rankings. The system performance was evaluated through manual calculation, Spearman coefficient correlation, and execution time test. The results showed that the implemented system is reliable and produces rankings that are consistent with manual calculation. A strong correlation was observed between Fuzzy VIKOR and Fuzzy TOPSIS rankings for cases with fewer criteria and alternatives, but it weakened as the complexity of the problem increased. In addition, the system showed that Fuzzy VIKOR had a faster overall execution time compared to the Fuzzy TOPSIS implementation. This indicates that the Fuzzy VIKOR method outperforms Fuzzy TOPSIS in terms of efficiency and computational speed. Overall, the developed DSS application helps decision makers in overcoming uncertainty and complexity in everyday decision making.